The trauma manual trauma and acute care surgery - Peitzman, Andrew B. (Lippincott manual, 2013)
Designed to be used as a quick reference, this multidisciplinary pocket guide addresses all areas of trauma and emergency surgery with a list of key points at the end of each chapter. In addition to a new section on the intensive care unit and an extended section on surgical emergencies, this manual also covers GI hemorrhage, hernias, bowel obstruction, pancreatitis, biliary tract disease, and other surgical challenges faced by trauma and emergency surgery personnel.Organized in a chronological fashion following the usual events and phases of care after injury or acute surgical illness, this user-friendly manual is one guide every trauma surgeon, surgical resident, surgical critical care specialist, emergency medicine physician, and emergency or trauma nurse, will want to keep close by.